On the Relationship Between Skepticism Towards and Reactance to Health Messages: The Special Case of Online Communication on Tick-Borne Encephalitis - Koinig, Isabell; Kohler, Sarah (Frontiers in Communication, 2021)
In general, health communication messages intend to change individuals’ behaviors, applying both cognitive reasoning and increasingly personal accounts to achieve these changes. Nonetheless, against the background of increasing skepticism towards scientific findings and patronizing message claims, health messages fail to achieve their intended results. By use of a quantitative survey with Austrian respondents (n= 271), the study at hand intends to uncover individuals’ level of skepticism towards Tick-Borne Encephalitis (TBE) as well as their evaluations of online vaccination-related information on TBE. Moreover, as skepticism is likely to lead individuals to reject health message content altogether, we also test for the relationship between skepticism and reactance. Results indicate that skepticism is only meagerly relevant in the TBE communication context. For this reason, other variables might have to be included in future research to derive more comprehensive results and recommendations. Since skepticism has proven to be of lesser importance in TBE message reception, government or health officials are recommended to prioritize additional constructs, such as trust, which can be elevated through more affective communication.